Highly active Co–Al2O3-based catalysts for CO2 methanation with very low platinum promotion prepared by double flame spray pyrolysis. Issue 20 (26th August 2016) - Schubert, Miriam; Pokhrel, Suman; Thomé, Andreas; Zielasek, Volkmar; Gesing, Thorsten M.; Roessner, Frank; Mädler, Lutz; Bäumer, Marcus
Abstract : Alumina supported Co catalysts are often promoted with noble metals to improve their reducibility and provide a high number of metallic Co sites. A flame spray pyrolysis based approach for the preparation is described which allows a fine dispersion of Pt so that very low concentrations are necessary. Abstract : Cobalt-based catalysts are often promoted with noble metals to improve the reducibility of the catalyst and provide a high number of metallic Co sites. The high cost of such noble metals requires new synthetic strategies enabling the use of such promoters at as low concentrations as possible. In this article, we present platinum-promoted Co–Al2 O3 catalysts with very small concentrations of platinum (between 0.03 and 0.43 wt%) synthesized by double flame spray pyrolysis (DFSP) as a very versatile preparation technique. Catalysts with Pt contents as low as 0.03 wt% Pt lead to a significant improvement in the reducibility of Co3 O4 and to high catalytic activity for the CO2 methanation reaction compared to non-promoted Co–Al2 O3 . Upon further increasing the Pt content up to 0.43 wt%, only a slight improvement in catalyst reduction and catalytic activity is observed. All prepared catalysts were characterised using XRD, BET, TPR, TEM and EDX followed by catalytic tests for CO2 methanation. Furthermore, two different preparation schemes were used for DFSP, where platinum was combusted either with Co or with the Al precursor solution in one flame, which results in catalysts with a tight chemical contact between Pt and Co3 O4 or Pt and Al2 O3, respectively. Based on TPR and catalytic tests it could be demonstrated that the deposition of platinum on one or the other oxidic phase has no influence on the reducibility and catalytic performance. The conversion and reducibility were similar for both preparation schemes, an observation which can be explained by H2 spillover during catalyst reduction and catalytic reaction.